ANALISIS KETERATURAN MATEMATIS PADA BUDAYA BANTEN - Etika Khaerunnisa; Yani Setiani; Isna Rafianti (Prima: Jurnal Pendidikan Matematika, 2018)
This research is motivated by the searching of banten cultural information which is viewed from mathematics aspect is still unfocus, whereas the culture contains the elements of mathematics, mathematics is the construction of the culture. The search for mathematical regularity in Banten culture can be a study that can be integrated in mathematics learning on transformation material. The research use descriptive qualitative research. Based on the results of research, on the object of Banten gate, Banten Great Mosque, Banten Tower, Banten traditional roof contains elements of reflection, dilatation, translation, symmetry, rotation. In Banten gate appears regularity of reflection, dilation, translation. At the grand mosque of Banten it appears the regularity of rotation, reflection, dilation. In the tower of Banten there is regularity of rotation, dilation, reflection. On the roof of the house Banten has the regularity of reflection, dilation, rotation. With the study of banten culture in terms of the concept of transformation, it can be used by teachers in learning mathematics on the transformation materials in schools, so that students are expected not only to achieve the knowledge competence related to transformation material, but also as a form of strengthening character education at nationalist value by having attitude competence love of its own culture can grow and be owned by students as national identity